Metagenome Analysis of the Bacterial Characteristics in Invasive Klebsiella Pneumoniae Liver Abscesses - Zhang, Zhijie; Wang, Hairui; Guo, Yawen; Liu, Zhaoyu; Chang, Zhihui (Frontiers in Cellular and Infection Microbiology, 2022)
Background Klebsiella pneumoniae liver abscess (KPLA) combined with extrahepatic migratory infection (EMI) is defined as invasive KPLA (IKPLA) and is associated with a poor prognosis. The mechanism of IKPLA formation is yet to be elucidated. In this study, metagenomic sequencing was used to compare the bacterial characteristics between IKPLA and KPLA to explore the underlying mechanism of invasiveness. Methods Clinical details, imaging, and microbial features were retrospectively evaluated by medical record review. Metagenomic sequencing was performed on the pus samples of liver abscesses whose culture results were indicative of monomicrobial Klebsiella pneumoniae (K. pneumoniae). Bacterial diversity and composition in IKPLA and KPLA were comparatively analyzed, and the key pathways and genes that may affect invasiveness were further explored. Results Sixteen patients were included in this study. Five patients with EMI were included in the IKPLA group, and the other eleven patients without EMI were assigned to the KPLA group. There was no statistical difference in the hypermucoviscous phenotype and serotype of K. pneumoniae between the two groups. The bacterial diversity of IKPLA was lower than that of KPLA. The abundant taxa in the IKPLA group were primarily species of unclassified Enterobacteriaceae and K. pneumoniae. The KPLA group had a high abundance of the genera Tetrasphaera and Leuconostoc. Metabolic pathway genes represented most of the enriched genes in IKPLA. Fourteen pathogenic genes with significant differences in abundance were identified between the two groups, including ybtS, fepC, phoQ, acrB, fimK, magA, entC, arnT, iucA, fepG, oqxB, entA, tonB, and entF (p < 0.001). Conclusion The diversity and bacterial composition of IKPLA were significantly different from those of KPLA. Microbiological changes in the abscess, activation of the related metabolic pathways, and the pathogenic gene expression may constitute a novel mechanism that regulates the invasiveness of KPLA.